Genetic Polymorphisms - New Insights 2022
DOI: 10.5772/intechopen.99482
|View full text |Cite
|
Sign up to set email alerts
|

HER2Ile655Val Polymorphism and Risk of Breast Cancer

Abstract: HER2 plays a vital role in the development and progression of several types of human cancer, so the HER2 becomes one of major targets for HER2-positive breast cancer treatment. Several reports have shown that the HER2 oncogene expression relates to clinicopathological factors in cancer patients. HER2Ile655Val single nucleotide polymorphism associates with malignant tumors, including prostate cancer, colorectal cancer, osteosarcoma, gastric cancer, uterine cervical carcinoma, fibroadenoma, and breast cancer. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 92 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…A growing body of evidence has demonstrated a remarkable genetic variation of the canine HER2 gene, with several SNPs being documented [ 20 , 21 , 24 , 25 ]. Nonetheless, although SNPs in the human HER2 gene have been associated with the susceptibility, clinical course, and response to treatment of breast cancer disease [ 37 , 38 , 39 ], the knowledge regarding the influence of HER2 SNPs on clinicopathological features and prognosis of CMT is still incomplete. In previous studies, our group demonstrated that SNP rs24537329 and rs24537331 in the canine HER2 gene were related to the CMT histotype, with the former being associated with the development of aggressive histological types, while the latter was related to less aggressive CMT histotypes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of evidence has demonstrated a remarkable genetic variation of the canine HER2 gene, with several SNPs being documented [ 20 , 21 , 24 , 25 ]. Nonetheless, although SNPs in the human HER2 gene have been associated with the susceptibility, clinical course, and response to treatment of breast cancer disease [ 37 , 38 , 39 ], the knowledge regarding the influence of HER2 SNPs on clinicopathological features and prognosis of CMT is still incomplete. In previous studies, our group demonstrated that SNP rs24537329 and rs24537331 in the canine HER2 gene were related to the CMT histotype, with the former being associated with the development of aggressive histological types, while the latter was related to less aggressive CMT histotypes [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…17 The polymorphism (I655V) present in the transmembrane region of HER2 is linked with an increased risk of breast cancer. 18 At codon 655, the conversion of Ile:ATC to V:GTC causes an increase in dimerization, tyrosine kinase activity, and autophosphorylation leading to cell transformation. 19 In HER2-positive…”
Section: Introductionmentioning
confidence: 99%
“…The polymorphisms in HER2 enhance the tyrosine kinase activity as well as increasing the formation of HER2 heterodimers that cause the progression of tumor 17 . The polymorphism (I655V) present in the transmembrane region of HER2 is linked with an increased risk of breast cancer 18 . At codon 655, the conversion of Ile:ATC to V:GTC causes an increase in dimerization, tyrosine kinase activity, and auto‐phosphorylation leading to cell transformation 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation